2010
DOI: 10.1042/bj20091589
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroceramide desaturase activity is modulated by oxidative stress

Abstract: Oxidative stress was previously implicated in regulation of ceramide metabolism. Here, its effects on dihydroceramide desaturase were investigated. To stimulate oxidative stress HEK293, MCF7, A549, and SMS-KCNR cells were treated with hydrogen peroxide, menadione, or tert-butylhydroperoxide. In all cell lines, an increase in dihydroceramide was observed upon oxidative stress as measured by LC/MS. In contrast, total ceramide levels were relatively unchanged. Mechanistically, dihydroceramide desaturase activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 36 publications
(44 reference statements)
2
50
1
Order By: Relevance
“…These results suggest that autophagy induced by SKI II is actually due to increases in dhCer rather than to decreased production of S1P, which occurs with both SKI II and PF543. Furthermore, increase in LC3 II was also the enzyme environment, which has been reported to affect this enzymatic activity ( 75 ). SKI II is a nonstructural analog of Des1 substrate and, as such, it does not probably directly interact with the Des1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that autophagy induced by SKI II is actually due to increases in dhCer rather than to decreased production of S1P, which occurs with both SKI II and PF543. Furthermore, increase in LC3 II was also the enzyme environment, which has been reported to affect this enzymatic activity ( 75 ). SKI II is a nonstructural analog of Des1 substrate and, as such, it does not probably directly interact with the Des1 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that sphingolipid changes resulting from dihydroceramide desaturase inhibition contribute to the COX2-independent, antiproliferating effect of celecoxib ( 19 ). Moreover, in a recent study, oxidative stress was shown to lead to accumulation of dihydroceramide due to dihydroceramide desaturase inhibition in several cell lines ( 21 ). Depletion of dihydroceramide desaturase by siRNA has shown to result in accumulation of dihydroceramides and G0/G1 cell-cycle arrest in neuroblastoma cells, suggesting a role for dihydroceramides in growth inhibition ( 10 ).…”
Section: Lipid Extraction and Mass Spectrometry Measurementsmentioning
confidence: 99%
“…On the other hand, until recently, the precursor of ceramide, dihydroceramide, was considered a bio-inert molecule, and a short-chain (C 2 ) dihydroceramide analog was used as a negative control in experiments to study the effects of ceramide ( 16,17 ). Recent studies using depletion or inhibition of dihydroceramide desaturase, which uses dihydroceramide as a substrate, changed the way we think about this concept ( 10,(18)(19)(20)(21)(22). Fenretinide and resveratrol treatments are reported to inhibit dihydroceramide desaturase and increase endogenous dihydroceramides, resulting in autophagy in cancer cells ( 10,20,22,23 ).…”
Section: Lipid Extraction and Mass Spectrometry Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A link between SL metabolism and ROS generation has been reported (22)(23)(24)(25). We now analyze ROS production in CerS2 null mouse liver.…”
mentioning
confidence: 99%